2006
DOI: 10.3354/ame043209
|View full text |Cite
|
Sign up to set email alerts
|

Significance of bacterivory and viral lysis in bottom waters of Franklin Bay, Canadian Arctic, during winter

Abstract: Little information is currently available about water column microbial processes or mortality during Arctic winter. To address this paucity, we used epifluorescence microscopy and dilution experiments to determine the abundance of flagellates, bacteria and virus-like particles (VLP) and the rates of bacterial growth, bacterivory and virus-induced mortality in subzero-temperature bottom waters (≤ 230 m) of Franklin Bay during February and March 2004, when ice-covered surface waters were highly oligotrophic (max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 45 publications
5
61
4
Order By: Relevance
“…This has not been observed in previous studies (Säwström et al 2007b, De Corte et al 2011. Finally, protist grazing in the Arctic community was higher than bacterial mortality due to viruses, as shown in Boras et al (2010), unlike in the Fjord community, where the impact of viruses on bacterial communities was higher than that of bacterivores, as shown by Wells & Deming (2006). These results suggest that both types of bacterial 'predators' could play an important role in controlling bacterial communities.…”
Section: Characteristics Of the In Situ Arctic And Fjord Waterssupporting
confidence: 41%
See 1 more Smart Citation
“…This has not been observed in previous studies (Säwström et al 2007b, De Corte et al 2011. Finally, protist grazing in the Arctic community was higher than bacterial mortality due to viruses, as shown in Boras et al (2010), unlike in the Fjord community, where the impact of viruses on bacterial communities was higher than that of bacterivores, as shown by Wells & Deming (2006). These results suggest that both types of bacterial 'predators' could play an important role in controlling bacterial communities.…”
Section: Characteristics Of the In Situ Arctic And Fjord Waterssupporting
confidence: 41%
“…Virus and bacterial numbers from the VP incubations were counted by flow cytometry. The number of viruses released by bacterial cells (burst size) was estimated from VP measurements, as in Middelboe & Lyck (2002) and Wells & Deming (2006). The increase in VA over short time intervals (4 h) in VP incubations was divided by the decrease in BA in the same time period.…”
Section: Viral Production and Bacterial Lossesmentioning
confidence: 99%
“…Viruses are pervasive in marine environments, causing microbial mortality at a rate equaling that caused by grazing (Steward et al 1996;Weinbauer and Höfle 1998;Wells and Deming 2006). Experimental studies show that although an increase in virus abundance can reduce growth rates in phytoplankton (Suttle et al 1990), viral lysis can ultimately lead to higher phytoplankton productivity (Peduzzi and Weinbauer 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies previously examining the impact of grazing versus viral lysis have focused on bacterial populations (Weinbauer and Peduzzi, 1995;Steward et al, 1996;Weinbauer and Höfle, 1998;Pedros-Alio et al, 2000;Jacquet et al, 2005;Fischer et al, 2006;Wells and Deming, 2006). These studies have shown that both viral lysis and grazing can cause significant mortality, but that the impact of each varies by season, host organism, and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…When bacterial cells are grazed, energy is made available to higher trophic levels, whereas when they are lysed, organic carbon and nutrients are dissolved and bacterial carbon is recycled as bacterial production in a closed loop (Middelboe et al, 1996;Wilhelm et al, 2002). Viruses have been shown to account for a high percentage of bacterial mortality in some marine environments (Weinbauer and Peduzzi, 1995;Wells and Deming, 2006;Taira et al, 2009), with percentages similar to those due to nanoflagellates when both sources of bacterial loss have been measured simultaneously (Fuhrman and Noble, 1995;Steward et al, 1996). Therefore, it is important to estimate both virus-and grazing-induced bacterial mortality to obtain better insight into the forces underlying nutrient flow within an aquatic food web.…”
Section: Introductionmentioning
confidence: 99%